Refúgio e imigração em São Paulo: uma análise através da realidade de cinco mulheres imigrantes negras - Almeida, Alexandra Cristina Gomes de (2021)
This work is result of the ethnography carried out in the city of São Paulo on the processes of integration and access to social rights for African, black women, asylum seekers, and immigrants. The research occurred in the same period that the consolidation of public policies aimed at the immigrant population by the city of São Paulo, a pioneering action, in the country. Issues such as class, race and gender were important in terms of the interlocutors' access to citizenship, placing them in a field of tensions and different forms of treatment and subordination. To understand this process, the work will bring an overview of brazil's main emergency agreements and political demands in the face of immigration, this explains that the historical legislative process on immigration has always been a selectivity in the population management of immigrants. This legislative history resonates in the current migratory flows and the experience of the women reveal obstacles to insert themselves in Brazilian society. Therefore, this work will problematize the experiences of women immigrants marked by power relations and hierarchies. which influence their circulation and access to the social, political and institutional spaces given to citizens.